The effect of the type of jaw growth caused by the change of baby teeth on the bioelectric activity of the chewing muscles - V. V. Shkarin; I. V. Didenko; Yu. A. Makedonova; S. V. Dmitrienko; E. N. Iarygina; A. G. Pavlova-Adamovich; E. A. Ogonyan (Эндодонтия Today, 2024)
INTRODUCTION. The bioelectric activity of the masticatory muscles is influenced by many factors due to the parameters of the craniofacial complex – morphometric parameters of the head. However, there is no data in the literature on the effect of the type of jaw growth during periods of alternating bite on the functional activity of the muscles that lift the lower jaw.AIM. To determine the impact of jaw growth type, associated with the transition from deciduous to permanent teeth, on the bioelectrical activity of the masticatory muscles.MATERIALS AND METHODS. A survey of 150 children aged 5 to 14 years was conducted, randomized into 5 groups – group I – the final period of milk bite and preparation of the jaw for tooth replacement. Group II – the first permanent molars and incisors of the lower jaw erupted. Group III – there was a change of permanent milk incisors. Group IV – there was a complete change of all baby teeth. Group V – the second permanent molars have erupted. An analysis of the telerentgenogram and the functional activity of the masticatory muscles is presented by determining absolute and relative indicators.RESULTS. In patients of groups I, II and III, low bioelectric activity was detected, which increases during the complete change of all baby teeth and the eruption of the second permanent molars, which is due to the formation of chewing activity of the muscles. Also, during this period, the symmetry and synchronicity of the work of the masticatory and temporal muscles proper was noted.CONCLUSIONS. Minimal changes during jaw growth due to the change of baby teeth lead to a change in the functional activity of the masticatory muscles, which may subsequently be a predictor factor for the development of neuromuscular imbalance in the maxillofacial region.